ANALISIS PENAWARAN TENAGA KERJA WANITA PADA SEKTOR INFORMAL DI KOTA JAMBI (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2017)
The study, entitled the analysis of labor supply of women in the informal sector in the city of Jambi. Jambi province's economic growth in the year 2009 - 2014 has an upward trend and the highest ever in the Sumatran for economic growth. Increased growth is followed by the growth of the informal sector in the city of Jambi. The informal sector is a lot of hiring women workers. This study uses primary data and secondary data as supporters. The study says that the informal sector absorbs tenga many women working in the city of Jambi. Income, age, education, and number of dependents greatly affect the labor supply of women in the informal sectors